Applied Theatre and Sexual Health: Apertures of Possibility, Katharine E. Low (2021). Issue 2 (1st November 2021) - Zontou, Zoe
Review of: Applied Theatre and Sexual Health: Apertures of Possibility, Katharine E. Low (2021)New York: Palgrave Macmillan, 323 pp., ISBN 978-1-349-95975-4, h/bk, €77.99